PERLINDUNGAN HUKUM TERHADAP JAMINAN AGUNAN DALAM PERJANJIAN KREDIT MODAL KERJA (KMK) (Studi Kasus Putusan No.466/Pdt.G/2020/PT.Mdn) - Ita Ita; Ayu Trisna Dewi; Rina Melati Sitompul (Universitas Dharmawangsa, 2022)
ABSTRACTThe thing which is the most disadvantaged party is the debtor, but it is possible that the bank as the creditor will also suffer losses from these problems.The problem in this research is how to regulate the law regardingthe debtor in the working capital credit agreement, how is the settlement process if the debtor is in default and how is the Judge's Consideration in Decision No. 466/Pdt/2020/PT MDN. This research method uses normative legal research and analytical descriptive research.The results of this study, legal arrangements regarding debtors in credit agreementsworking capital based on the provisions of Article 1338 of the Civil Code. The process of settling debtors with outstanding performance in a credit agreement can be carried out by saving credit through rescheduling, reconditioning and restructuring. Furthermore,settlement of credit by means of the execution of the executive title by the creditor, sale of objects to be objects of collateral through auctions, sales of collateral in underhand. The judge's consideration in the decision no. 466/2020/PT.MDN, namely the plaintiff or defendant I, must comply with the agreement that has been agreed uponincluding the existence of the plaintiff's bad credit, which should be Defendant I submitting a default suit to the Binjai District Court or submitting a request for execution to the Binjai District Court or other courts anywhere within the territory of the Republic of Indonesia, instead of submitting it to another institution, namely to Defendant II to resolve legal issues between the plaintiff and Defendant I.It is recommended that the creditor must be able to anticipate things that are done to the debtor due to default by conducting deliberation to find the best solution, moreover the debtor has good faith to pay the pending debt in accordance with the agreement that has been made.Keywords: Legal Protection, Guarantee, Credit Agreement